2003
DOI: 10.1002/cne.10795
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of mammalian brain aging: Distribution of cathepsin D–immunoreactive cell bodies and dystrophic dendrites in aging dogs resembles that in Alzheimer's disease

Abstract: Elevated levels of the lysosomal enzyme cathepsin D are found in the early stages of Alzheimer's disease (AD) and co-occur with intraneuronal tangles. The present study tested whether increases in cathepsin D would emerge during aging in another mammalian species. Regional brain patterns of cathepsin D immunostaining were compared in dogs ages 0.35 to 16 years. Accumulations of immunopositive material were evident in neuronal cell bodies in many forebrain sites in middle-age to old dogs (>/=6 years). Three typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…15,41,42 While the hippocampal slice model has identified an association between protein accumulation and synaptopathogenesis, 32,37 slice cultures show that lysosomal activation occurs as well (Fig. 5A).…”
Section: Resultsmentioning
confidence: 95%
“…15,41,42 While the hippocampal slice model has identified an association between protein accumulation and synaptopathogenesis, 32,37 slice cultures show that lysosomal activation occurs as well (Fig. 5A).…”
Section: Resultsmentioning
confidence: 95%
“…First, conditions that interfere with normal operation cause lysosomes to proliferate, something that in some neurons leads to large accumulations of fused, dense secondary bodies in the periphery of the cell body. This process appears to be responsible for the formation of meganeurites (Bednarski et al, 1997) and similar structures found in primary dendrites ('dendritic spikes', Bi et al, 2003). These pathological features likely disrupt transport between the cell body and its processes by displacing and distorting the tubule system.…”
Section: Relationship Of Plasticity Deficits To Generalized Brain Agingmentioning
confidence: 97%
“…Increases in autophagosomes/autolysosomes were confirmed by electron microscopy analysis, as numerous membranous vacuoles with double membranes or multilamellar electron-dense material are observed in the cytoplasm of Purkinje cells in Npc1 -/-mice. We previously reported changes in lysosomal function in the brains of middle-aged and aged mammals, 20,21 and decreases in lysosomal function have been hypothesized to produce increases in autophagosomes in brains with Alzheimer's disease. 22,23 It is thus conceivable that changes in lysosomal function induced by accumulation of cholesterol in Npc1 -/-brains reduce the turnover of autophagic vacuoles leading to a buildup of these organelles.…”
Section: Lysosomal Dysfunction Jams Autophagic Machinery and Aggravatmentioning
confidence: 99%